Barley molybdenum cofactor sulfurase (MCSU): sequencing, modeling, and its comparison to other higher plants - ALTINKUT UNCUOĞLU, AHU (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2015)
Molybdenum cofactor sulfurases (MCSUs) are important enzymes for plant development and response to environmental queues, including processes such as nitrogen metabolism and regulation of the abscisic acid levels in plant tissues. We cloned and sequenced MCSU gene from barley and performed in silico comparison with rice, tomato, and Arabidopsis. Physico-chemical properties and subcellular predictions were found to be similar in different plant species. All MCSUs had three critical domains: aminotransferase class-V (Pfam: PF00266), MOSC N-terminal beta barrel (Pfam: PF03476), and MOSC (Pfam: PF03473). Secondary structure analysis revealed that random coils were the most abundant, followed by alpha-helices and extended strands. Predicted binding sites of MCSUs were different in barley and Arabidopsis, whereas rice and tomato showed the same pattern. A conserved triple-cysteine motif was detected in all MCSUs with cys438-cys440-cys445, cys431-cys433-cys438, cys428-cys430-cys435, and cys425-cys427-cys432 in barley, rice, Arabidopsis, and tomato, respectively. Furthermore, a 3D structure analysis indicated that structural divergences were present in all MCSUs, even in the core domain structure. Phylogenetic analysis of MCSUs revealed that monocot-dicot divergence was clearly observed with high bootstrap values. The results of this study will contribute to the understanding of MCSU genes and proteins in plants. The data of this study will also constitute a scientific basis for wet-lab and in silico studies of MCSUs.
Keywords: Barley; in silico analysis; molybdenum cofactor sulfurase; sequencing; 3D structure; plant protein; THALIANA PROVIDES INSIGHT; NIFS-LIKE DOMAIN; STRUCTURE PREDICTION; ALDEHYDE OXIDASE; LOCUS ENCODES; PROTEIN; GENE; ABA3; BIOSYNTHESIS; MECHANISM